Officer Appearance and Perceptions of Police: Accoutrements as Signals of Intent. (16th March 2018) - Simpson, Rylan
Abstract: The present research experimentally evaluates the effects of vests, gloves, batons, sunglasses, and hats on perceptions of police officers as aggressive, approachable, friendly, respectful, and accountable. The results reveal a plethora of findings, which together suggest that variation in officer appearance elicits variation in perceptions of officers. For example, high-visibility vests exhibit positive effects on perceptions of officers. Black gloves, longstick batons, and sunglasses, in contrast, exhibit negative effects on perceptions of officers. Load-bearing vests exhibit mixed effects and baseball hats exhibit no significant effects. Accoutrements as signals of intent are important means by which police exude presence and nonverbally communicate their philosophies and intentions to the public. Practitioners and academics alike should consider these perceptual effects when examining the police-perception nexus. By strategically equipping and deploying officers in appropriate aesthetics, police departments may enhance their relations with the public.